The role of phosphorus in agriculture (American Society of Agronomy, 1980)
Proceedings of a symposium held 1-3 June 1976 at the National Fertilizer Development Center, Tennessee Valley Authority, Muscle Shoals, Alabama, cosponsored by the Tennessee Valley Authority ... [et al.]. The objectives of the symposium were to assemble recognized authorities to summarize current knownledge about phosphorus as it relates to agriculture and to provide an authoritative reference work on this subject.